Analisa Komentar Siswa Tentang Minat Melanjutkan Pendididkan di Universitas Stella Maris Sumba pada SMA Plus Umma Katukku - Diana Lia Bora; Gergorius Kopong Pati; Paulus Mikku Ate (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
State regulations state that village funds come from the State Budget (APBN) and are used to support governance, development, development, and social activities as well as community empowerment. It is hoped that the existence of village funds will increase the sources of income for each village, and the addition of village income by the government will improve public service facilities.1. As a result, a sentiment analysis of village officials will be carried out in this study. The Naive Bayes approach will be used to classify public sentiment as part of this investigation. We will evaluate two methods to see which produces more accurate results. In addition, the village government's function as the most important social institution in the community is essential for setting standards, facilitating socialization, and allocating resources. Furthermore, some Eweta community members have not received assistance, which could cause social rivalry among neighbors. Through sentiment categorization, responses will be categorized as either positive or negative. Based on feedback from visitors, this study attempts to assess the validity of the two approaches put to the test and offer insights into the caliber of services rendered by the village administration.